The Impact of Vibration on the Accuracy of Digital Surveying Instruments - Hossam El-Din Fawzy (Salehan Institute of Higher Education, 2019)
A digital surveying instrument has a crucial and effective role in civil engineering. These digital surveying instruments have contributed to providing quick and simplified solutions to solve many surveying problems: particularly accuracy, saving time, and effort .Therefore, the main objective of this research is the study of the vibrations effect on digital devices efficiency during the observation process, which occur frequently especially when the devices occupy the bridges during observation or when the occupation of the device is set nearby the railways, as well as in construction sites with heavy equipment movement. Although most digital surveying instruments contain a compensator device, this research find out through the experimental test that the effect of vibration on the accuracy of observation results and the noticed errors may extend to many centimeters. In case of using the digital level devices (SOKKIA SDL-30) under exposure to vibration (up to 20 KHZ/Sec), the average error of elevation was 36.9 mm in 80 m distance and the maximum standard deviation elevation error was 18.26 mm. But in the case of using the reflector-less total station (SOKKIA SET330RK) under exposure to vibration (from 7.5 to 15 KHZ/Sec), the average error of positioning was 79.95 mm in 85 m distance and the maximum standard deviation positioning error was 43.41 mm.